2019
DOI: 10.1002/pssb.201900368
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ga–OH Bond at Initial GaN Surface on the Electrical Characteristics of SiO2/GaN Interface

Abstract: Herein, the influence of the Ga-OH bond at the GaN surface on the electrical characteristics of the SiO 2 /GaN metal-oxide semiconductor structure is investigated. The GaN surface is modified by three different surface treatments (O 2 annealing, wet annealing, and ultraviolet [UV]/O 3 treatment). The Ga-OH bond is evaluated by X-ray photoelectron spectroscopy and characterized by capacitance-voltage (CV) measurements and a positive bias stress test. Increasing the ratio of Ga-OH bonds at the SiO 2 /GaN interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…All spectra feature two peaks shifted by approximately 1.5 eV. This peak separation is consistent with previous studies (0.6–1.5 eV). The peaks are located at 530.5 and 531.9 eV and denote the Ga–O (attributed to the O 2– anions of the crystalline network) and Ga–OH (oxides with lower electron density, i.e., O – or OH – , and greater covalent character) components, respectively. As-made galinstan microdroplets feature a high abundance of the Ga–O component (denoting the native gallium oxide).…”
Section: Resultssupporting
confidence: 88%
“…All spectra feature two peaks shifted by approximately 1.5 eV. This peak separation is consistent with previous studies (0.6–1.5 eV). The peaks are located at 530.5 and 531.9 eV and denote the Ga–O (attributed to the O 2– anions of the crystalline network) and Ga–OH (oxides with lower electron density, i.e., O – or OH – , and greater covalent character) components, respectively. As-made galinstan microdroplets feature a high abundance of the Ga–O component (denoting the native gallium oxide).…”
Section: Resultssupporting
confidence: 88%
“…(We note that the presence of some adsorbed water cannot be excluded.) The energy difference between the hydroxide and oxide peaks was within the reported range (0.6–1.5 eV). , The total oxygen coverage corresponds to an areal density of 1.5 × 10 15 cm –2 (Table ). This points to a thin surface layer with a thickness close to that of a monolayer.…”
Section: Results and Discussionsupporting
confidence: 63%
“…In this study, our objectives are GaN power semiconductor devices, which have attracted much attention in recent years, while many issues still remain at the MOS interface. 11,12 One of the challenges is how to reduce the electrical interface defects measured by the interface state density, D it , which represents the quality of an interface. D it is strongly affected by the surface condition of the GaN substrate and the deposition conditions of plasma-enhanced chemical vapor deposition (PECVD), which deposits SiO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…D it is strongly affected by the surface condition of the GaN substrate and the deposition conditions of plasma-enhanced chemical vapor deposition (PECVD), which deposits SiO 2 . For improving the surface of GaN, previous research reported a significant reduction of D it values by introducing the operation of UV/O 3 treatment to the surface of GaN . As deposition conditions for PECVD, five process variables exist: temperature, pressure, radio frequency (RF) power, oxygen flow rate, and precursor material (TEOS) flow rate.…”
Section: Introductionmentioning
confidence: 99%